A Twisted Bay‐Substituted Quaterrylene Phosphorescing in the NIR Spectral Region. Issue 11 (24th October 2017) - Miletić, Tanja; Fermi, Andrea; Papadakis, Ioannis; Orfanos, Ioannis; Karampitsos, Nikolaos; Avramopoulos, Aggelos; Demitri, Nicola; De Leo, Federica; Pope, Simon J. A.; Papadopoulos, Manthos G.; Couris, Stelios; Bonifazi, Davide
Abstract : The preparation of the first soluble quaterrylene derivative featuring peripheral tert ‐butyl substituents and sterically hindering, core‐anchored triflate groups has been achieved. This involves a facile synthetic route based on an oxidative coupling of perylene precursors in the presence of H2 O2 as oxidant. The steric hindrance between the TfO substituents at the central bay position of the quaterrylene board triggers a strong deformation of the central perylene planarity, which forces the quaterrylene platform to adopt a twisted geometry as shown by X‐ray analysis. Exceptionally, photophysical investigations show that the core‐twisted quaterrylene phosphoresces in the NIR spectral region at 1716 nm. Moreover, third‐order nonlinear optical measurements on solutions and thin film containing the relevant molecule showed very large second hyperpolarizability values, as predicted by theoretical calculations at the CAM‐B3LYP/6‐31G** level of theory, making this material very appealing for photonic applications. Abstract :